Religious Minorities in Pakistan: Constitutional Rights, Social Realities, and the Quest for Inclusive Citizenship - Abdul Malik Gopang; Irfan Ali Katohar; Jawad Ali (Journal of Religion and Society, 2026)
Pakistan's religious minorities Hindus, Christians, Ahmadis, Sikhs, and Kalash communities constitute approximately four percent of the national population yet confront a stark paradox while the 1973 Constitution enshrines robust guarantees of religious freedom, equality, and non-discrimination, persistent social, legal, and political barriers systematically undermine their full enjoyment of inclusive citizenship. This article critically examines this constitutional-social disconnect through a mixed-methods qualitative-dominant approach integrating doctrinal legal analysis of constitutional provisions, landmark judicial rulings, and empirical documentation of lived realities drawn from human rights reports, scholarly literature, and case studies of violence and discrimination. The central thesis contends that Pakistan's secular-Islamic constitutional hybrid, though progressive on paper, has been eroded by majoritarian nationalism, judicial inconsistency, and weak enforcement mechanisms that render constitutional protections conditional rather than substantive. Analysis reveals that Articles 20, 25, 27, and 36 of the Constitution face systematic circumvention through blasphemy law misuse, electoral mechanisms that dilute minority political voice, educational curricula that frame non-Muslim identities as peripheral, and state institutions that routinely fail to prevent or prosecute forced conversions, mob violence, and attacks on minority places of worship. Intersectional dimensions encompassing gender, class, and regional variations across Punjab, Sindh, and Khyber Pakhtunkhwa compound these vulnerabilities, producing differentiated experiences of marginalization that demand context-specific policy responses. The article proposes pathways toward inclusive citizenship grounded in Maqasid al-Sharia frameworks that reconcile Islamic identity with pluralism, advancing procedural blasphemy law reforms, electoral system redesign, curriculum transformation, and an empowered National Minority Commission with enforcement authorities. By bridging constitutional analysis with social realities, this study contributes to South Asian minority-rights discourse while offering evidence-based recommendations for translating Pakistan's constitutional promises into substantive belonging. Keywords: religious minorities, constitutional rights, social exclusion, blasphemy laws, inclusive citizenship, Pakistan